The new reader’s eye-scan and the intermedial processes - Osian, Aida Elisabeta (Creativity Studies, 2012)
Within the field of meaning (re)production, the newly fashioned media theories have been stemming from Marshall McLuhan’s and Mikhail Bakhtin‘s “hybrids” and generating what we are presently experiencing as flexible theoretical phenomena, exposed to immediate change and constant altering, due to the overflow of media-related materialities. Orbiting the ancient concept of ekphrasis, this study aims to immerse the product resulted from the literary description of a work of art in the conceptual works-in-progress known as intermediality and remediation. The aspects directly addressed here are: what is the place of ekphrasis within the pertinence axis of intermediality? To what extent can the ekphrastic exercise be considered in terms of remediation? Throughout the study we will be making use of several excursions into the postmodern narrative with the intent to advocate for a reconsideration of the ekphrastic process and for the requirement of a new image-to-text mapping and its outcome in the digital age. Naujojo skaitytojo akis-skaitytuvas ir intermedialūs procesai Santrauka. Reikšmės (re)produkcijų lauke naujamadės medijų teorijos, kilusios iš Marshallo McLuhano ir Michailo Bachtino „hibridų“, lemia tai, ką nūdien patiriame kaip lanksčius teorinius fenomenus, atvirus staigiems pokyčiams ir nuolatinėms permainoms, esant medijų skleidžiamos informacijos perviršiui. Šis tyrimas, telkiamas apie senąjį ekphrasis konceptą, siekia įtraukti meno kūrinio literatūrinio aprašymo rezultatus į konceptualų procesualumą, dar vadinamą intermedialumu ir remediacija. Čia tiesiogiai aptariami šie aspektai: kokia ekphrasis vieta tikėtinoje intermedialumo ašyje? Kokiame kontekste ekfratinė praktika gali būti svarstoma remediacijos terminais? Tyrime padarysime keletą ekskursų į postmodernųjį naratyvą, siekdami persvarstyti ekfratinį procesą, naująjį teksto vertimo vaizdu reikalavimą ir jo rezultatus skaitmeniniame amžiuje. Reikšminiai žodžiai: ekphrasis, hibridiškumas, tarpmeninė poetika, intermedialumas, remediacija, transmedialumas.